Approaches for sustainable preservation of Heze String Music - Zhao, Tingting; Yeoh, Joanne Pei Sze; Loo, Fung Chiat (Human Resource Management Academic Research Society, 2023)
This study delves into the cultural, educational, and technological intersections of Heze String Music, a rich traditional art form deeply rooted in Chinese history. While the intricate sounds of the Heze instruments once reverberated primarily within confined cultural spaces, there is a pressing need for its integration into contemporary education systems to ensure its continuity. Through ethnographic fieldwork, interviews, and immersion in both urban and rural settings, the researcher explored the current developmental trends of Heze String Music, its reception among the youth, and its adaptive strategies for survival in a rapidly modernizing world. Key findings reveal a dual challenge: maintaining the authenticity of the music while adapting to modern pedagogical techniques and digital platforms. Educational institutions play a pivotal role in this endeavor, offering structured curricula designed to foster appreciation and skills in Heze music. Community-based programs and digital engagements further bolster efforts to bridge the generational divide, ensuring the music remains resonant in today's digital age. This study underscores the significance of evolving traditional art forms through modern education paradigms, highlighting the holistic benefits of such integrative approaches.